Mechanisms Of The Algerian Legislator To Organize Tournaments And Sports Competitions, In Accordance With Law 05/13 Relating To Sport - Lemmouchi , Abdessalam; Taibi , Ammar (sports creativity, 2025)
This study aims to try to clarify the mechanisms put in place by Law 05/13 to organize sports events in the different types of sports included therein, to determine the file of their organization, the criteria to be fulfilled in the installation sport in which the event will be organized, and the mechanisms put in place to prevent possible violence during a sporting event. By adopting the descriptive method and the content analysis tool as the main research tool to analyze the different materials related to sporting events, we concluded at the end of the study that the legislator responded to the ambiguity that surrounds previous sports legislation by providing effective protection for athletes during and on the occasion of sports events by Law 13/05. , Organize Tournaments, Law 05/13 Relating To Sport Mechanisms